Transformation of dynamic aspects of UML models into LOTOS behaviour expressions - Hnatkowska, Bogumiła; Huzar, Zbigniew (Zielona Góra: Uniwersytet Zielonogórski)
The lack of formal semantics for the UML creates many ambiguity problems, especially when real-time systems are specified. The paper proposes an approach to a formal definition of UML statecharts. Main features of the UML statecharts are described, and next, a transformation of the UML statecharts into LOTOS is defined.
Keywords: statecharts; UML; LOTOS